2017
DOI: 10.1017/jfm.2017.537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a surface tension imbalance on a partly submerged cylinder

Abstract: We perform a static analysis of a circular cylinder that forms a barrier between surfactant-laden and surfactant-free portions of a liquid-gas interface. In addition to determining the general implications of the balances for forces and torques, we quantify how the imbalance γ = γ a − γ b between the uniform surface tension γ a of the surfactant-free portion of the interface and the uniform surface tension γ b of the surfactant-laden portion of the interface influences the load-bearing capacity of a hydrophobi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In addition to this, previous studies showed that liquid surface tension contributes to the object's buoyancy force. As a result, elongated hydrophobic objects are able to float in spite of its high overall density [127] . Since wetting can lead to water permeation, hydrophobic materials are ideal solution to be used as a floating platform due to its low surface energy and wettability [128] .…”
Section: Floating Dynamicmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, previous studies showed that liquid surface tension contributes to the object's buoyancy force. As a result, elongated hydrophobic objects are able to float in spite of its high overall density [127] . Since wetting can lead to water permeation, hydrophobic materials are ideal solution to be used as a floating platform due to its low surface energy and wettability [128] .…”
Section: Floating Dynamicmentioning
confidence: 99%
“…As a result, elongated hydrophobic objects are able to float in spite of its high overall density. [127] Since wetting can lead to water permeation, hydrophobic materials are ideal solution to be used as a floating platform due to its low surface energy and wettability. [128] When a hydrophobic material is in contact with water, meniscus is formed around the edges of the object and is proportional to the object's cross section perimeter bounded by the triple line.…”
Section: Floating Dynamicmentioning
confidence: 99%
“…However, the horizontal resultant force will be non-zero if considering a surface tension imbalance on the cylinder (Janssens et al. 2017).…”
Section: Hysteresis Effect and Force Analysis On A Concave Cylindermentioning
confidence: 99%
“…The surface tension imbalance can induce the twisting of a Janus cylinder (Oratis, Farmer & Bird 2017). The surface tension imbalance also can induce self-powered locomotion of a hydrogel water strider (Zhu et al 2021) or an isotropic particle with different surface tension coefficients on its surface (for example, a partially submerged cylinder having surface tension imbalance; see Janssens, Chaurasia & Fried (2017)). Even if convex to the fluids, a Janus particle, half of which has a different contact angle from the other half, possibly has a jump of contact line at its surface when it moves through a fluid-fluid interface.…”
Section: Concave Shapes With Concave Partsmentioning
confidence: 99%
See 1 more Smart Citation